2008
DOI: 10.1080/09603100701720393
|View full text |Cite
|
Sign up to set email alerts
|

Macro shocks and the Japanese stock market

Abstract: The article investigates to what extent various underlying macro (oil, supply, demand and portfolio) shocks impact the fluctuations of Japanese stock prices by developing a multivariate structural vector autoregression (SVAR) model. The results from a Markov regime-switching (MS) specification of the underlying shocks reveal that these shock-generating processes are characterized by nonlinearity with varied turning points and fit well with the actual historical events. Demand shocks, as opposed to supply shock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 28 publications
1
7
1
Order By: Relevance
“…Odusami (2009) showed that returns on crude oil futures have a negative impact on the US stock market returns. Similar results provide Faff and Brailsford (1999) for Australia, Papapetrou (2001) and Hondroyiannis and Papapetrou (2001) for Greeceas well as Huang & Guo (2008) for Japan. But Cong et al (2008) documented that oil price shocks have not a statistically significant impact on the stock market indices in China, with the exception of the manufacturing index and some oil companies.…”
Section: Literature Reviewsupporting
confidence: 73%
“…Odusami (2009) showed that returns on crude oil futures have a negative impact on the US stock market returns. Similar results provide Faff and Brailsford (1999) for Australia, Papapetrou (2001) and Hondroyiannis and Papapetrou (2001) for Greeceas well as Huang & Guo (2008) for Japan. But Cong et al (2008) documented that oil price shocks have not a statistically significant impact on the stock market indices in China, with the exception of the manufacturing index and some oil companies.…”
Section: Literature Reviewsupporting
confidence: 73%
“…Similarly, Park and Ratti (2008) show that an increase in oil price volatility significantly depresses real stock returns for 12 European countries. A negative relationship between oil price behavior and stock market returns is reported in numerous studies, such as Miller and Ratti (2009) for six OECD countries, Papapetrou (2001) for Greece, and Huang et al (2005), and Huang and Guo (2008) for Japan.…”
Section: Literature Reviewmentioning
confidence: 95%
“…Most of the existing research on the relationships between energy prices and the macro economy has mainly focused on the relationship between crude oil prices and economic growth (Hamilton, 2003;Bachmeier, 2008). However, it is surprising that only a relatively small amount of the literature has studied the relationship between oil price shocks and stock markets (Jones and Kaul, 1996;Huang et al, 1996;Huang and Guo, 2008). These studies fail to reach a unanimous conclusion.…”
Section: Introductionmentioning
confidence: 95%